Positive Surgical Margin Status after Minimally Invasive Radical Prostatectomy: a Multicenter Study. Issue 4 (October 2015) - Tafa, Ardit; Grasso, Angelica; Antonelli, Alessandro; Bove, Pierluigi; Celia, Antonio; Ceruti, Carlo; Crivellaro, Simone; Falsaperla, Mario; Minervini, Andrea; Parma, Paolo; Porreca, Angelo; Zaramella, Stefano; et al.
Aim: The aim of our study is to evaluate the status of positive margins (PSMs) comparing their incidence between aparoscopic radical prostatectomy (LRP) and robot assisted radical prostatectomy (RARP) in centers with medium case-load (50–150 cases/year). We also analyzed the correlations between surgical technique, nerve-sparing approach (NS), and incidence of PSMs, stratifying our results by pathological stage. Materials and methods: We analyzed 1992 patients who underwent RP in various urologic centers. We evaluated the incidence of PSMs, and then we compared the stage-related incidence of PSMs, for both the techniques. Results: We did not find a statistically significant difference between the two surgical modalities in the study regarding the overall incidence of PSMs. Conclusions: In our retrospective study, we did not find any difference in terms of PSMs in RARP versus LRP. Our PSMs were not negligible, particularly in pT3 stages, compared with high-volume centers; surgical experience and patients' selection can be a possible explanation.